Bioactive Brominated Metabolites from the Natural Habitat and Tank‐Maintained Cuttings of the Jamaican Sponge Aplysina fistularis. Issue 6 (18th June 2013) - Gallimore, Winklet A.
Abstract Cut specimens of the common reef sponge of the Verongid family, Aplysina fistularis, were retained in flow‐through seawater tanks over a six‐week period to assess the metabolite profile of the sponge when subjected to stress, compare the profile with the source material, and assess the preliminary feasibility of the protocol for sponge culture. The living specimens were harvested, extracted with MeOH/CH2Cl2 1 : 1, and subjected to column chromatography to identify metabolites. The brominated isoxazoline compounds, aerothionin (1) and 11‐oxoaerothionin (2), along with aeroplysinin 2 (3) and 2‐(3, 5‐dibromo‐4‐hydroxyphenol)acetamide (4), were detected in the cuttings from the tank‐maintained sponge. An examination of the metabolite profile of the sponge from the natural habitat showed that the compounds 1 and 2 were present. The identities of all the compounds were ascertained by analysis of the mass‐spectral data and NMR spectra (1H, 13C, HMBC, and HSQC) of the compounds, which were compared with reported data. The survival rate was 44% with limited necrosis or exposed skeletal tissue being observed in eight of the 18 cuttings, suggesting that protocol modifications would be required for culturing the sponge.